Post dismissal earning and reduction of monetary compensation for unfair dismissal in Malaysia - Ali Mohamed, Ashgar Ali; Shair Mohamad, Mohd Akram; Sardar Baig, Farheen Baig (International Organization Center of Academic Research (OCERINT) Publishing, 2017)
At common law, a wrongfully dismissed workman is bound to make reasonable exertion and show diligence in endeavouring to procure alternative employment. Failure to accept suitable alternative employment or take reasonable steps to procure the same would result in a deduction from the total amount recoverable for unfair dismissal calculated on a sum representing the amount the workman might have earned during the period. If the workman is unable to secure a comparable job, or where a comparable job did not exist having regard to the nature of his responsibilities and skill requirement, rate of pay and the location, he is not bound to accept such employment nor will a reduction be warranted. The burden is on the employer to present credible evidence that it is more likely than not that the workman failed to mitigate the loss, and the court will consider the steps taken by the workman to mitigate the loss. In Malaysia, the Industrial Court is required to reduce or scale down the back wages when there was a post dismissal earning after the dismissal, a percentage of such earning shall be deducted from the back wages. The Court should take into account all relevant matters including the fact, where it exists, that the workman has been gainfully employed elsewhere after his dismissal. An employee who has not been gainfully employed since his dismissal, or who has been gainfully employed but on a woefully small salary, should clearly say so to the court. To remain silent is to risk the court making a deduction deemed reasonable by the court. Apart from the duty to mitigate loss, the quantum of deduction, the factors that need to be considered and the sum that the employee will finally receive is equally important to be discussed. In light of the above, this paper discusses the duty of the employee to mitigate the loss following an unfair dismissal and the quantum of deduction with reference to the practice in Malaysia and United Kingdom.